Pendidikan Moderasi Beragama di Indonesia (Wacana dan Kebijakan) - M Mukhibat; Ainul Nurhidayati Istiqomah; Nurul Hidayah (Southeast Asian Journal of Islamic Education Management, 2023)
Currently there are many social conflicts that arise due to differences in religion and belief. Therefore it is important for government agencies to make a breakthrough program to deal with these situations and conditions. One of the programs that has been implemented is the religious moderation program that has been echoed by the Indonesian Ministry of Religion since 2016. This research aims to dig deeper regarding the religious moderation policy in Indonesia that has been implemented by the Indonesian Ministry of Religion, especially in the field of education. By using the literature study research method, the results of the research show that as a multicultural country, Indonesia has a variety of ethnicities, cultures and religions, so that this diversity has the potential to create conflict between ethnic, cultural and even religious groups. Therefore, mainstreaming religious moderation appears as an alternative to establishing peace between people in diversity. Religious moderation education policies are carried out in the framework of maintaining inter-religious harmony in Indonesia with the main objective of reducing intolerance, religious fanaticism and extremism that can threaten social stability and national security. In the context of globalization and technological advances, religious moderation education can help students understand the role of religion in modern life and how to develop positive values ??from religion.